Seroprevalence of HIV in acute Orthopaedic trauma at the Johannesburg Hospital - Sefeane, Tatolo Ishmael (My University, 2011)
The principal aim of the study was to establish the HIV Seroprevalence in an acute Orthopaedic trauma setting in an urban teaching hospital. Secondary aims were (i), to establish if the seroprevalence compares with the national averages and findings from other similar studies, and (ii), to establish the effect of informed consent on the response rate to recruitment in HIV related studies. Methodology All illegible patients (able and qualified to give an informed consent for HIV testing) admitted to the Orthopaedic trauma unit at the Johannesburg hospital, were pre-counselled and tested for HIV after admission. Those that tested positive were then counselled again and referred accordingly to the HIV clinics for follow up. Results A total of 797 patients were admitted during the period. 159 (20%) did not meet the inclusion criteria, declined counselling or could not be counselled for various reasons. The main reason for non response was cited as a need to wait until after the acute event before they considered the test. A total of 648 patients were therefore eligible for recruitment. All patients were pre-counselled for the test and 246 (39%) consented and signed the informed consent form. Of those that were tested, 57 (23%) tested positive and were followed up accordingly. This result was then compared with previous non Orthopaedic studies on the HIV Seroprevalence. The rate of HIV infection in our acute orthopaedic trauma setting was found to be 23%. This is higher than the national averages but compares with other studies. Most acutely traumatized patients are not willing to be tested for HIV in the acute setting. This has a huge bearing on recruitment of suitable candidates for future studies in HIV in an acute trauma setting. Higher response rates to recruitment in HIV studies are directly proportional to the use of qualified counsellors in organized centres like the Voluntary Counselling and Testing centres.
Keywords: HIV; Orthopedics